Solution of Fuzzy Fractional Integro-Differential Equations Using A Domian Decomposition Method (Journal of Informatics and Mathematical Sciences, 2017)
In this paper, we present Adomian decomposition method to solve linear fuzzy fractional integro-differential equation with fuzzy initial conditions. Results are compared with the results obtained using Fuzzy Laplace transform method.
Keywords: Adomian decomposition method; Fractional integro-differential equation; Fuzzy differential equations